2013
DOI: 10.5455/2320-1770.ijrcog20130606
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of 296 cases of intra uterine fetal deaths at a tertiary care centre

Abstract: Background: To identify the risk factors and to streamline preventive and management protocols for IUD. Methods: This was a retrospective study from January 2011 to December 2012 which was conducted at G.S.V.M. Medical College, Kanpur. IUD was defined as fetal death beyond 20 weeks of gestation and/or birth weight > 500g. Maternal and fetal records were analysed. Mode of delivery and associated complications were studied. Results: Total number of deliveries were 7310.Incidence of IUD at our centre was 40 per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 18 publications
8
34
2
1
Order By: Relevance
“…Although the perinatal mortality has reduced over last few decades, the intrauterine fetal deaths still remain exceptionally high. 8 The incidence of IUFD in our study was found to be 36.17/1000 live births, In the study from upper part of India conducted by Singh N et al 9 incidence was 40/1000, while in the study conducted by Patel S et al 10 incidence was 22.2/1000 live birth. Rate of stillbirths vary greatly in different studies and regions.…”
Section: Discussionsupporting
confidence: 42%
“…Although the perinatal mortality has reduced over last few decades, the intrauterine fetal deaths still remain exceptionally high. 8 The incidence of IUFD in our study was found to be 36.17/1000 live births, In the study from upper part of India conducted by Singh N et al 9 incidence was 40/1000, while in the study conducted by Patel S et al 10 incidence was 22.2/1000 live birth. Rate of stillbirths vary greatly in different studies and regions.…”
Section: Discussionsupporting
confidence: 42%
“…It was observed in the present study that 19.5% fetal deaths were in this category. Neetu singh et al found 33% unexplained fetal deaths in their study of 296 cases of IUFD [10]. These deaths occur in late pregnancies and sometimes even in women with regular antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum number of IUFD occurred in primi (44.5%) , followed by second gravida (37.5%) 3 rd gravida10% and in 4 th and 5 th gravida it was 7% respectively. In the study by neetu singh et al 7 it was found that the incidence was maximum in primigravida (25%) followed in order 17%, 18% and 24% in grandmultiparity according to increase in parity.…”
Section: Discussionmentioning
confidence: 99%
“…There were 19.5% women where no causative factor was found for intrauterine fetal demise. Singh Neetu et al 7 found 33% unexplained fetal deaths in their study of 296 cases of IUFD Over the years the causative factors responsible for IUFD have changed. There was an observation that not only the incidence is reducing in developed countries, but the patterns of etiologies are also changing syphilis and other infections are no longer significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation